Determinants of Job Satisfaction among Working Caregivers of People with Disabilities: The Roles of Self-Efficacy, Job Autonomy, and Outcome Expectancy - Abdul Rahman, Segufta Yasmi; Masnita, Yolanda; Prestianawati, Silvi Asna; Abdul Wahat, Nor Wahiza; Abdul Rahim, Nur Aira; Sabri, Mohamad Fazli (International Review of Management and Marketing, 2026)
Job satisfaction remains a critical concern in Human Resource Development (HRD) as it influences employee well-being, organizational commitment, and workforce sustainability. However, limited empirical attention has been given to employees who simultaneously perform caregiving roles for people with disabilities. This study addresses this gap by examining the determinants of job satisfaction among employed caregivers of people with disabilities in Selangor, Malaysia. Drawing upon the Model of Work Satisfaction (Lent & Brown, 2006) and the Model of Proactive Behavior (Crant, 2000), the study investigates the effects of self-efficacy, personality traits, outcome expectancy, perceived organizational support, job autonomy, and learning goal orientation on job satisfaction. Learning goal orientation was also examined as a mediating mechanism linking individual and organizational factors to job satisfaction. A quantitative correlational research design was adopted, and data were collected from 325 working caregivers. The data were analyzed using covariance-based structural equation modeling (CB-SEM). The findings reveal that self-efficacy, outcome expectancy, and job autonomy significantly influence job satisfaction, with self-efficacy emerging as the strongest predictor. These findings contribute to discussions on decent jobs, inclusive economic growth, and economic productivity by highlighting the importance of sustainable employment conditions for working caregivers. The study contributes to HRD literature by extending existing models of work satisfaction to a caregiving context and provides practical implications for organizations seeking to create inclusive and supportive workplaces aligned with Sustainable Development Goal 8 (Decent Work and Economic Growth).